Significant Differences in Physicochemical Properties of Human Immunoglobulin Kappa and Lambda CDR3 Regions - Townsend, Catherine L.; Laffy, Julie M. J.; Wu, Yu-Chang Bryan; Silva O’Hare, Joselli; Martin, Victoria; Kipling, David; Fraternali, Franca; Dunn-Walters, Deborah K. (Frontiers in Immunology, 2016)
Antibody variable regions are composed of a heavy and a light chain and in humans there are two light chain isotypes: kappa and lambda. Despite their importance in receptor editing, the light chain is often overlooked in the antibody literature, with the focus being on the heavy chain CDR-H3 region. In this paper, we set out to investigate the physicochemical and structural differences between human kappa and lambda light chain CDR regions. We constructed a dataset containing over 29,000 - light chain variable region sequences from IgM-transcribing, newly formed B cells isolated from human bone marrow and peripheral blood. We also used a published human naïve dataset to investigate the CDR-H3 properties of heavy chains paired with kappa and lambda light chains, and probed the Protein Data Bank (PDB) to investigate the structural differences between kappa and lambda antibody CDR regions. We found that kappa and lambda light chains have very different CDR physicochemical and structural properties, whereas the heavy chains with which they are paired do not differ significantly. We also observed that the mean CDR3 N nucleotide addition in the kappa, lambda and heavy chain gene rearrangements are correlated within donors, but can differ between donors. This indicates that TdT may work with differing efficiencies between different people, but the same efficiency in the different classes of immunoglobulin chain within one person. We have observed large differences in the physicochemical and structural properties of kappa and lambda light chain CDR regions. This may reflect different roles in the humoral immune response.